A Photographic Record of Snail Activity - Dorothy E. Beetle (Hello World!, 1970)
Freshwater snails in their natural habitat move slowly over the vegetation and substrate, exhausting the patience of an observer trying to record their activity. At infrequent intervals they exhibit, for mollusks, rapid motion, travelling a distance of several yards in a few minutes. Occasionally they drop from the tinderside of 'the surface film or ascend rapidly. The approach of another individual of the same species can result in short period's of investigative behavior that sometimes leads to mating. A snail moves with slow dispatch.